Implementasi Kebijakan Penerimaan Peserta Didik Baru (PPDB) Jalur Zonasi dalam Mewujudkan Pemerataan Akses Pendidikan: Studi Kasus di SDN Jagakarsa 12 Jakarta Selatan - Marur Chamim; Estika Sari; Achmad Ardiansyah; Luthfi Fadilah (PT Cendekia Education Center, 2026)
The New Student Admission (PPDB) policy through zoning is the government's effort to realize equitable access to education. However, its implementation still faces various challenges, such as inequality in the distribution of students, public perception of favorite schools, and administrative constraints. This study aims to analyze the implementation of the zoning policy in SPMB at SDN Jagakarsa 12, identify supporting and inhibiting factors, and examine its impact on equal access to education. The research uses a qualitative approach with a descriptive method. Data was collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study show that the implementation of the zoning path policy at SDN Jagakarsa 12 has been carried out according to the provisions and is supported by regulations, human resources, and adequate facilities and infrastructure. However, obstacles are still found in the form of public perception of favorite schools, delays in self-reporting, disruptions of the online registration system, and attempts to manipulate domicile. This policy has a positive impact on the ease of access and efficiency of education costs, but also limits school choice for some people. Therefore, it is necessary to strengthen socialization, improve the quality of services between schools, and administrative supervision to support equal distribution of education.